Update on Autism Spectrum Disorders for Optometry: A Review of the Literature. - Jensen, Kristi A.; Hoppe, Elizabeth; Remick-Waltman, Kristy; Spors, Frank; Egan, Donald (Optometry & Visual Performance, 2014)
Background: The purpose of the paper is to review current literature on Autism Spectrum Disorders (ASD) and to inform doctors of optometry who will provide care for patients with ASD and their families. As primary care providers, it is important that doctors of optometry have the knowledge and skills required to recognize the signs and symptoms of ASD and to contribute to the multi-disciplinary team for diagnosis and treatment. Methods: A review and synthesis of current relevant literature was conducted. Results: Publications describing the epidemiology of autism, risk factors, screening, and diagnosis are reviewed. Optometry is not currently listed as one of the multi-disciplinary professions in the ASD team, and this article proposes potential roles of the doctor of optometry to fill in the missing piece in the coordination of care of ASD patients. Conclusions: Doctors of optometry should play an important role in the care of individuals with ASD. It is time that optometrists assume their role as primary care providers to care for vulnerable populations such as individuals on the autism spectrum. Optometrists should be aware of current diagnostic criteria and research regarding patterns of autism and potential risk indicators. Familiarity with types of healthcare providers, local community resources, and screening and diagnostic tools that can assist both in making a definitive diagnosis and in managing autism spectrum disorders is important for the optometric provider.